Implementasi Program ‘LENTERA’ Dalam Membentuk Karakter Islami - Mumtaz, Rizky Nisrina; Laela, Faizah Noer (Jurnal Ilmiah Wahana Pendidikan, 2025)
On the basis of the above thoughts and facts, this research is focused on answering several fundamental dimensions, namely the role of schools in shaping Islamic character, the form of implementation of the 'LENTERA' program, and the evaluation of the implementation of the 'LENTERA' program carried out by Parlaungan Islamic Junior High School. This type of research uses a qualitative-literature review method by explaining the phenomena that occur related to the variables taken by the researcher. Then the qualitative method is used to measure and assess the relationship between the variables studied. The content of this research focuses on the LENTERA program carried out at Parlaungan Islamic Junior High School in shaping the Islamic character of students by paying attention to some literature. The reality is that worship is not just knowing and understanding, but must be implemented. Several universities, both public and private, have collaborated to provide material on character building. However, most of them only bring from their respective points of view and are optimized by teachers, because teachers know more about the character of students can be concluded several important points. First, helping students in terms of strengthening faith and piety, as well as producing children with good character. Second, Islamic character building is not only developed at school, but also at home. Third, the 'LENTERA' program emphasizes the formation of student character, such as attitude, communication, behavior, time management, manners to meet teachers and friends, and enthusiasm in worshiping five times.